Design, synthesis and biological evaluation of 1,3-dihydroxyxanthone derivatives: Effective agents against acetylcholinesterase - Menéndez, Cintia Anabella (2017)
The present work concerns the rational design and development of new inhibitors of acetylcholinesterase (AChE) based on the privileged xanthone scaffold. In order to understand and rationalize the mode of action of these target structures a theoretical study was initially conducted. From the results of rational design, a new variety of amphiphilic xanthone derivatives were synthesized, structurally characterized and evaluated as potential anti-Alzheimer agents. The results showed that most of the synthesized compounds exhibited high AChE inhibitory activity at the micromolar range (IC50, 0.46–12.09 μM). The synthetic xanthone 11 showed the best inhibitory effect on AChE and a molecular modeling study revealed that 11 targeted both the catalytic active site (CAS) and the peripheral anionic site (PAS) of AChE. Therefore, this compound could be considered as a potential lead compound towards new drugs for the treatment of Alzheimer’s disease.